Resident doctors’ views on generic medicines: A study on knowledge, attitude and practice - SONALI SURYAWANSHI; KALYANI KHADE; PRITI DHANDE; VIJAYA PANDIT (International Journal of Pharma and Bio Sciences, 2019)
In developing countries like India, the cost of medicines is a major concern. To control healthcare expenditure promoting the use of cheaper generic drugs instead of the more expensive branded equivalents can be implemented. For this, it is important to create an awareness of generic medicines among doctors. Hence, this study was planned to evaluate the knowledge, attitude and practices of resident doctors of a tertiary care hospital regarding the use of generic medicines and identifying factors favoring and restricting the use of the same. It was a cross-sectional study with a questionnaire of 26 items, designed to assess the knowledge, attitude and practices about generic medicines. All data were analyzed with SPSS (version 19.0) and results were depicted in the form of percentages and graphs. 57% of participants believed that generic medicines were as effective aIn developing countries like India, the cost of medicines is a major concern. To control healthcare expenditure promoting the use of cheaper generic drugs instead of the more expensive branded equivalents can be implemented. For this, it is important to create an awareness of generic medicines among doctors. Hence, this study was planned to evaluate the knowledge, attitude and practices of resident doctors of a tertiary care hospital regarding the use of generic medicines and identifying factors favoring and restricting the use of the same. It was a cross-sectional study with a questionnaire of 26 items, designed to assess the knowledge, attitude and practices about generic medicines. All data were analyzed with SPSS (version 19.0) and results were depicted in the form of percentages and graphs. 57% of participants believed that generic medicines were as effective as corresponding branded ones but only 24% of them were willing to switch to generics in their prescription practices. Nearly 3/4th of the study population was aware of the fact that the active ingredients of generic drugs were similar to that of its branded counterpart but many of them lacked knowledge about its similar dosage form/formulation, dose/strength and indication for use. More than 80% of resident doctors considered efficacy and safety profile of any product while writing prescriptions. A significant knowledge gap was noted with regards to generics among the resident doctors in spite of their good attitude towards generic medicines. Programs should be implemented to increase awareness about generic drugs’ quality and availability.s corresponding branded ones but only 24% of them were willing to switch to generics in their prescription practices. Nearly 3/4th of the study population was aware of the fact that the active ingredients of generic drugs were similar to that of its branded counterpart but many of them lacked knowledge about its similar dosage form/formulation, dose/strength and indication for use. More than 80% of resident doctors considered efficacy and safety profile of any product while writing prescriptions. A significant knowledge gap was noted with regards to generics among the resident doctors in spite of their good attitude towards generic medicines. Programs should be implemented to increase awareness about generic drugs’ quality and availability.